ANALISIS FAKTOR-FAKTOR FUNDAMENTAL PERUSAHAAN YANG MEMPENGARUHI TENURE AUDITOR: Studi Empiris pada Perusahaan Bank, Pembiayaan, Asuransi dan Efek di Bursa Efek Indonesia tahun 2005-2014 - Suparlan, SE., M.Sc.A Suparlan (LPPM Universitas Gunung Rinjani, 2019)
This study aimed to get empirical evidence of firm characteristics influence on AUDITORTENURE. Corporatre governance which are essential parts that run the company. The dataused in this research is secondary data using population Non-banking company, CreditAgencies Other Than Banks, Securities, Insurance and investment according to theclassification of Indonesian Capital Market Directory (ICMD) listed on the Stock Exchange. Inthis study using purposive sampling using sampling. Furthermore, in order to test thehypothesis, this study took a sample pairs (matched-pairs sample) among the companies thatchanged the company KAP KAP is not changed. Total sample of this study using the 450companies with details of changed KAP 225 and 225 do not change KAP. The results of thisstudy found that public ownership, Share growth and the size of the company has astatistically significant relationship with Wald greater than the value of α of 5% which meansthat affect the probability of companies do change KAP. But the size of the company has theopposite direction to the hypothesis of the study, so it is not able to support the hypothesis.Meanwhile, institutional ownership, the number of commissioners and leverage does not giveeffect to the company to change KAP